(y-zx)p+(x+yz)q=x2+y2
"\\frac{dx}{y-xz}=\\frac{dy}{x+yz}=\\frac{dz}{x^2+y^2}=t\\\\\ndx=yt-xzt,\\quad dy=xt+yzt,\\quad dz=(x^2+y^2)t\\\\\nydx+xdy=y^2t-xyzt+x^2t+xyzt=(x^2+y^2)t\\Longrightarrow\\\\\n\\frac{ydx+xdy}{x^2+y^2}=\\frac{dz}{x^2+y^2}=t\\Longrightarrow\\\\\ndz=ydx+xdy\\Longrightarrow z'_x=y,\\quad z'_y=x \\Longrightarrow z(x,y)=xy+c;\\\\\ncheck:\\\\\n(y-xz)p+(x+yz)q=(y-x\\cdot (xy+c))\\cdot z'_x + (x+y\\cdot (xy+c))\\cdot z'_y=\\\\\ny^2-xy(xy+c)+x^2+xy(xy+c)=x^2+y^2;"
Comments
Leave a comment